2019
DOI: 10.1530/endoabs.63.p1125
|View full text |Cite
|
Sign up to set email alerts
|

Both comorbidity burden and low testosterone can explain symptoms and signs of testosterone deficiency in men consulting for sexual dysfunction

Abstract: Sexual Dysfunction a useful correlate to define a symptomatic LOH. 3,5-7 By restricting the construct of LOH to those having both TD and the aforementioned sexual symptoms, the figure of its representation in Europe is dramatically reduced, i.e., 2.1% of the European general population older than 40 years. 3 The presence of a specific association between sexual symptoms and TD is not enough to establish the direction of the relationship; in fact, it is possible that TD is responsible for causing the symptoms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…To evaluate the comorbidity burden of sexual symptoms compatible with T deficiency in subjects consulting for sexual dysfunction, we used a validated aggregate comorbidity measure, termed “chronic disease score” (CDS), which reflects the weighted number of medications used by the patients. We found that several symptoms and signs, potentially associated with LOH, could be due to chronic illnesses, occasionally present in subjects with sexual dysfunction 11 …”
Section: Testosterone and Male Sexualitymentioning
confidence: 79%
See 3 more Smart Citations
“…To evaluate the comorbidity burden of sexual symptoms compatible with T deficiency in subjects consulting for sexual dysfunction, we used a validated aggregate comorbidity measure, termed “chronic disease score” (CDS), which reflects the weighted number of medications used by the patients. We found that several symptoms and signs, potentially associated with LOH, could be due to chronic illnesses, occasionally present in subjects with sexual dysfunction 11 …”
Section: Testosterone and Male Sexualitymentioning
confidence: 79%
“…Although low T is only one of the factors associated with reduced libido 38 (see also Figure 3B), this symptom is rather specific to the condition of LOH. In fact, by using Chronic Disease Score (CDS), a widely accepted measure of comorbidities, we found that several LOH correlates‐—such as reduced penile blood flow, severe ED, reduced spontaneous erection, and related psychological burden—are relatively unspecific for LOH because they could be ascribed either to low T or to age‐associated morbidities 11 . However, this is not the case for HSD 11 .…”
Section: Testosterone and Other Aspects Of Male Sexuality In Lohmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike classical hypogonadism, functional hypogonadism usually presents a more subtle clinical picture, with non‐specific symptoms and usually no overt signs of androgen deficiency. Furthermore, these symptoms often overlap with those arising from co‐existing co‐morbidities and the effects of ageing in older men . Nevertheless, sexual complaints, such as decreased libido, morning erections or erectile dysfunction (ED), were more frequently associated with low T in community‐dwelling middle‐aged and elderly European men .…”
Section: Methodsmentioning
confidence: 99%